Die nordostarktische Fischerei im Jahre 2003 - Schöne, Rüdiger; Ulleweit, Jens (2003)
Seasampling of the important northeast Arctic fish stocks cod, saithe, haddock, redfish and Greenland halibut was continued in 2003. The sampling is part of the European data sampling directive on commercial fisheries established in recent years. This directive is relevant for European waters as well as for other areas where quotas have been assigned for European community member states. Furthermore, the results of these samplings are used as German basic data for stock assessments of the “Arctic Fisheries Working Group” of the International Council for the Exploration of the Seas (ICES). This report presents results of biological investigations which were carried out in ICES divisions IIa and IIb on board FMS “KIEL” in January/February and July/August 2003. The last section summarizes results and recommendations on the scientific assessment of the northeast Arctic fish stocks.